An Overview of the Cellular Mechanisms of Flavonoids Radioprotective Effects - Mahdi Mashhadi Akbar Boojar (Tabriz University of Medical Sciences, 2020)
Considering the remarkable application of radiotherapy in the treatment and diagnosis of various diseases and even nuclear war, it is important to protect healthy tissues and people at risk from the radiation. Currently, there is no ideal and safe radioprotective agent available and we are seeing a great effort to find these agents from natural sources. Phenolic compounds, as well as flavonoid, are presented widely as the second metabolite in plants and they have been considered for investigation according to their benefits for human health, healing and preventing many disorders. The major bioactive benefits of flavonoids include antioxidant, anti-inflammatory, anti-tumor, anti-aging, anti-bacterial and viral, neuroprotection and radioprotective effects. Their lower toxicity and oral administration have made it suitable for radiotherapy patient, radiation, military forces, and even the general public. This review attempts to provide a summary of the main molecular mechanisms involved in flavonoid radio-protective effects. Data of these studies will provide a comprehensive perspective to flavonoids and can help to optimize their effects in radioprotection procedures.